PERILAKU PENCEGAHAN HIV PADA REMAJA: LITERATURE RIVIEW - Dwi Nilamsari; Nina Pamelasari (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
HIV/AIDS represents a significant public health issue that continues to present challenges, particularly for the adolescent population, who are experiencing a sensitive phase of psychological and social development. Adolescents tend to be more vulnerable to HIV transmission, often triggered by risky sexual activity, deficient understanding, limited access to data, and the strong influence of peer groups. This investigation was designed to analyze the determinants impacting HIV prevention practices among adolescents, based on a compilation of literature from various studies at both the domestic and global levels. The methodological approach adopted was a literature review, involving an in-depth evaluation of research articles related to HIV prevention behaviors among adolescents. The findings of this analysis indicate that HIV prevention behaviors are influenced by three fundamental categories of factors: personal factors factors (including knowledge, affinity, self-efficacy, and assessment of potential dangers), family factors (including support, interpersonal dialogue, and parenting styles), and social milieu factors (the role of peers, information media, and access to health services). The study also found that educational interventions, adolescent counseling, strengthening family support, and increasing access to accurate information play a significant role in improving prevention behaviors. This study emphasizes the importance of a comprehensive approach involving families, schools, and communities to foster more effective HIV prevention behaviors in adolescents